FENOMENA CHILDFREE DALAM PANDANGAN HUKUM ISLAM PERSPEKTIF MAQASHID AL-SYARI’AH DAN RELEVANSINYA DENGAN HARTA WARIS - Taufiq Ramadhan; Wahida Aulia Fahrani (Universitas Darunnajah Jakarta, Indonesia, 2024)
Marriage as a sacred bond between a man and a woman, is meant to produce offspring and the continuation of human life. However, not all couples want to have children or choose to be childfree. This phenomenon raises questions about the ideal concept of marriage in Islam towards childfree and its implications for inheritance. This study aims to determine the concept of marriage, the phenomenon of childfree, and its impact on inheritance in the perspective of Maqashid al-syari'ah. By using a qualitative method with a type of literature review research, this research analyzes the Islamic perspective on childless marriages, emphasizing the importance of maintaining human lineage (hifdz an-nasl) and protecting property (hifdz al-mal). The results of this research are: 1) The concept of ideal marriage in Islam related to protecting offspring (hifdz an-nasl) and protecting property (hifdz al-mal) aims to create a family that is prosperous materially and spiritually. 2) That having children is recommended in Islam, but not an obligation, and childfree is allowed as long as it does not conflict with the objectives of Islamic law. If childfree is contrary to Maqashid al-syari'ah, then it is prohibited. 3) For heirs who are childfree, the impact of inheritance can involve changes in the distribution of inherited property.